2015
DOI: 10.2147/copd.s77662
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic obstructive pulmonary disease among never-smokers in Korea

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) patients include those who have never smoked. However, risk factors other than smoking in never-smokers have not been elucidated sufficiently. This study investigated the risk factors for COPD among never-smokers in Korea using population-based data.MethodsThe data were retrieved from the Korean National Health and Nutrition Survey IV conducted from 2007 to 2009. Among subjects aged 40 years or older who underwent appropriate pulmonary function tests, neve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 52 publications
(82 reference statements)
9
43
0
8
Order By: Relevance
“…The increase in COPD prevalence is similar to findings from the fourth KNHANES (2007–2009) and indicated that the average prevalence in these 3 years was 7.6% [10]. It has been reported that the prevalence of COPD among nonsmoking adults aged ≥ 40 years in China is 5.2% [12], which is slightly lower than the rate in South Korea.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The increase in COPD prevalence is similar to findings from the fourth KNHANES (2007–2009) and indicated that the average prevalence in these 3 years was 7.6% [10]. It has been reported that the prevalence of COPD among nonsmoking adults aged ≥ 40 years in China is 5.2% [12], which is slightly lower than the rate in South Korea.…”
Section: Discussionsupporting
confidence: 82%
“…A study that analyzed 2007–2009 KNHANES data also showed a 4.2-times higher incidence rate in men than in women [10], and a study on Chinese nonsmoking adults showed that the rate was 1.97 times higher in men [11]. Men could be at higher risk due to a lower level of health-related information or a lower rate of practicing health-related behavior than women [10], and are more occupationally and environmentally exposed to hazardous substances [12].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations